2020
DOI: 10.1186/s12889-020-09110-9
|View full text |Cite
|
Sign up to set email alerts
|

Why under five children are stunted in Pakistan? A multilevel analysis of Punjab Multiple indicator Cluster Survey (MICS-2014)

Abstract: Background: Pakistan is facing a serious problem of child under-nutrition as about 38% of children in Pakistan are stunted. Punjab, the largest province by population and contributes high gross domestic product (GDP) share in economy has reported 27% moderately and 10% severely stunted children of less than 5 years. Thus, this study aims at examining the determinants of stunting (moderate and severe) at different level of hierarchy empirically in Punjab province of Pakistan. Methodology: Data for this study is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 57 publications
6
26
0
2
Order By: Relevance
“…The information from this analysis is in line with previous research in South Africa and Pakistan (Mahmood et al, 2020;Mkhize and Sibanda, 2020). Lack of sanitation facilities is also informed as a determinant of the stunted toddler (Mahmood et al, 2020).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The information from this analysis is in line with previous research in South Africa and Pakistan (Mahmood et al, 2020;Mkhize and Sibanda, 2020). Lack of sanitation facilities is also informed as a determinant of the stunted toddler (Mahmood et al, 2020).…”
Section: Resultssupporting
confidence: 83%
“…The information from this analysis is in line with previous research in South Africa and Pakistan (Mahmood et al, 2020;Mkhize and Sibanda, 2020). Lack of sanitation facilities is also informed as a determinant of the stunted toddler (Mahmood et al, 2020). Not only applies to toddlers, but improper sanitation is also reported to be one of the factors affecting the nutritional status of adolescent girls in Eastern India (Chattopadhyay et al, 2019).…”
Section: Resultssupporting
confidence: 82%
“…Data from demographic and health survey and Multi-indicator Cluster Surveys datasets from 84 countries findings are consistent with our analysis and shows the prevalence for being wasted, stunted, and concurrently wasted and stunted among children less than five years 4 . Similar survey findings revealed that child age, birth order, education of parents, poor sanitation facilities and poverty are associated significantly with the likelihood of moderate and severe stunting in one of the province of Pakistan 6 , 33 . Study supported our findings that the families with choice of male babies could results malnourished and underweight babies in their families 34 .…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, it has been reported about 6 million children were stunted and wasted 4 . LBW is highly prevalent in particularly south Asian countries like, India, Pakistan and Bangladesh 2 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The information from this analysis is in line with previous research in South Africa and Pakistan (Mahmood et al, 2020; Mkhize and Sibanda, 2020). Lack of sanitation facilities is also informed as a determinant of the stunted toddler (Mahmood et al, 2020). Not only applies to toddlers, but improper sanitation is also reported to be one of the factors affecting the nutritional status of adolescent girls in Eastern India (Chattopadhyay et al, 2019).…”
Section: Resultsmentioning
confidence: 99%